М
Молодежь
К
Компьютеры-и-электроника
Д
Дом-и-сад
С
Стиль-и-уход-за-собой
П
Праздники-и-традиции
Т
Транспорт
П
Путешествия
С
Семейная-жизнь
Ф
Философия-и-религия
Б
Без категории
М
Мир-работы
Х
Хобби-и-рукоделие
И
Искусство-и-развлечения
В
Взаимоотношения
З
Здоровье
К
Кулинария-и-гостеприимство
Ф
Финансы-и-бизнес
П
Питомцы-и-животные
О
Образование
О
Образование-и-коммуникации
Angela11001
Angela11001
26.01.2021 02:42 •  Алгебра

Из формулы v=m/p выразите p через v и m

👇
Ответ:
lol1044
lol1044
26.01.2021
Крест-накрест переносишь, получаешь: p=m/v
4,5(89 оценок)
Открыть все ответы
Ответ:
йцукен56
йцукен56
26.01.2021
First, we'll try to plug in the value:
#lim_{x to -oo}x+sqrt(x^2+2x) = -oo + sqrt(oo-oo)#
We're already encountering a problem: it is simply not allowed to have #oo-oo#, it's like dividing by zero.
We need to try a different approach.
Whenever I see this kind of limit, I try to use a trick:
#lim_{x to -oo}x+sqrt(x^2+2x)#
#= lim_{x to -oo}x+sqrt(x^2+2x)*(x-sqrt(x^2+2x))/(x-sqrt(x^2+2x))#
These are the same becaus the factor we're multiplying with is essentially #1#.
Why are we doing this? Because there exists a formula which says: #(a-b)(a+b) = a^2-b^2#
In this case #a = x# and #b = sqrt(x^2+2x)#
Let's apply this formula:
#lim_{x to -oo}(x^2-(sqrt(x^2+2x))^2)/(x-sqrt(x^2+2x))#
#= lim_{x to -oo}(x^2-x^2-2x)/(x-sqrt(x^2+2x))#
#= lim_{x to -oo}(-2x)/(x-sqrt(x^2+2x))#
Now we're going to use another trick. We'r going to use this one, because we want to get the #x^2# out of the square root:
#lim_{x to -oo}(-2x)/(x-sqrt(x^2(1+2/x))#
If you look carefully, you see it's the same thing.
Now, you might say that #sqrt(x^2) = x#, but you have to remember that #x# is a negative number. Because we're taking the positive square root, #sqrt(x^2) = -x# in this case.
#= lim_{x to -oo}(-2x)/(x+xsqrt(1+2/x))#
#= lim_{x to -oo}(-2x)/(x(1+sqrt(1+2/x)))#
We can cancel the #x#:
#= lim_{x to -oo}(-2)/(1+sqrt(1+2/x))#
And now, we can finally plug in the value:
#= -2/(1+sqrt(1+2/-oo))#
A number divided by infinity, is always #0#:
#= -2/(1+sqrt(1+0)) = -2/(1+1) = -2/2 = -1#
This is the final answer.
Hope it helps.
4,7(80 оценок)
Ответ:
rafik321
rafik321
26.01.2021

3х-у=3, 2. 2х-3у=1, 3. 2х+у=1, 4. х+у=6,

3х-2у=0. 3х+у=7. 5х+2у=0. 5х-2у=9.

5. х+5у=7, 6. х+у=7, 7. 4х-3у=-1, 8. х+2у=-2,

3х+2у=-5. 5х-7у=11. х-5у =4. 3х-у=8.

9. 2х-5у=-7, 10. х-у=3, 11. 3х-5у=16, 12. 2х+3у=-7,

х-3у=-5. 3х+4у=2. 2х+у=2. х-у=4.

13. 2х+5у=-7, 14. х-3у=8, 15. 2х-3у=5, 16. х-4у=-1,

3х-у=15. 2х-у=6. х-6у=-2. 3х-у=8.

17. 5х-4у=12, 18. 6х+у=5, 19. 2х-3у=11, 20. х-6у=-2,

х-5у=-6. 2х-3у=-5. 5х+у=2. 2х+3у=11.

21. 3х-2у=16, 22. 2х+3у=3, 23. 4х-2у=-6, 24. 3х+2у=8,

4х+у=3. 5х+6у=9. 6х+у==11. 2х+6у=10.

25. 5х+у==14, 26. 3х-2у=5, 27. х+4у=7, 28. 2х-3у=5,

3х-2у=-2. 2х+5у=16. х-2у=-5. 3х+2у=14.

29. х-2у=7, 30. 4х-6у=26, 31. х+3у=7, 32. 8х+3у=-21,

х+2у=-1. 5х+3у=1. х+2у=5. 4х+5у=-7.

33. х-2у=8, 34. 8х+2у=11, 35. 2х-у=13, 36. 7х+3у=1,

х-3у=6. 6х-4у=11. 2х+3у=9. 2х-6у=-10.

37. 2х+3у=10, 38. 3х-2у=5, 39. 2х+у=-5, 40. 2х+3у=1,

х-2у=-9. 5х+4у=1. х-3у=-6. 6х-2у=14.

4,6(94 оценок)
Это интересно:
logo
Вход Регистрация
Что ты хочешь узнать?
Спроси Mozg
Открыть лучший ответ